Noise And Oscillations In Biological Systems: Multidisciplinary Approach Between Experimental Biology, Theoretical Modelling And Synthetic Biology - Morelli, Luis Guillermo (2012)
Rapid progress of experimental biology has provided a huge flow of quantitative data, which can be analyzed and understood only through the application of advanced techniques recently developed in theoretical sciences. On the other hand, synthetic biology enabled us to engineer biological models with reduced complexity. In this review we discuss that a multidisciplinary approach between this sciences can lead to deeper understanding of the underlying mechanisms behind complex processes in biology. Following the mini symposia “Noise and oscillations in biological systems” on Physcon 2011 we have collected different research examples from theoretical modeling, experimental and synthetic biology.